The Development of Scientific Learning Model Based on Local Wisdom of "Piil Pesenggiri" to Improve Process Skills and Character Values of Elementary School Students - Fitri April Yanti; Moh. Irma Sukarelawan; M. Anas Thohir; Ryzal Perdana (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims: to produce a learning model based on Local Wisdom Piil Pesenggiri knowledge that has characteristics that can improve the process skills and values of elementary school characters, produce a science learning model based on Piil Pesenggiri Local Wisdom based on appropriate knowledge to improve process skills and values of elementary school character, produce a model of science learning based on Piil Pesenggiri Local Wisdom which is effective for improving the process skills and characters values of elementary school. This research using the ADDIE step of the Research and Development method. The trial subjects included elementary school grade IV students in Lampung Province. Need assessment data is collected by interview, questionnaire, and observation. The feasibility data of the learning model were collected using a validation sheet questionnaire. Data were analyzed descriptively and statistically. This study's results are expected to make the model of learning science-based on local wisdom Piil Pesenggiri can lead to the development of a learning science model on local wisdom in other regions throughout Indonesia. This development is expected to help students be more interested in learning, understanding their own culture, and becoming students who have good character values.